An empirical analysis of sector-wise private investment for a small open economy. Issue 1 (31st December 2022) - Abbas, Ahsan; Abbas, Zaheer; Mustifa, Ghulam
ABSTRACT: The present study empirically analyses the sector-wise private investment behaviour in Pakistan using the autoregressive distributed lag model from 1964 to 2015. The results indicate that credit availability and infrastructural development considerably affect private investment in agriculture, industry, and services. However, the user cost of capital does not have any influence on investment. The response of investment demand to credit availability is inelastic (i.e. 0.259) for agriculture but relatively higher for the industrial sector with a magnitude of 0.554. However, its value is slightly higher than the unit elastic value (1.059) in services. Fertiliser use positively impacts investment in agriculture, which is negatively affected by access to water. The values of the corresponding coefficients are 0.726 and −2.731, respectively. Remittances and foreign direct investment positively contribute to private investment in services. Openness significantly demotes private investment in services, and its magnitude is relatively high (−5.127). The findings signify and implicate the role of water availability, government support, and financial development in the agricultural sector. However, a stable political environment and cost of investment are very important for investment activities in the industry. Nevertheless, the role of openness in investment in services is vital.